2021
DOI: 10.3389/fimmu.2020.609490
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Indoleamine 2,3-Dioxygenase in Cancer Models Using the Novel Small Molecule Inhibitor NTRC 3883-0

Abstract: Indoleamine 2,3-dioxygenase (IDO1) is a key regulator of immune suppression by catalyzing the oxidation of L-tryptophan. IDO1 expression has been related to poor prognosis in several cancers and to resistance to checkpoint immunotherapies. We describe the characterization of a novel small molecule IDO1 inhibitor, NTRC 3883-0, in a panel of biochemical and cell-based assays, and various cancer models. NTRC 3883-0 released the inhibitory effect of IDO1 on CD8-positive T cell proliferation in co-cultures of IDO1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Targeting those immune checkpoint molecules is a common anti-tumor strategy currently used in cancers. Other strategies are also proposed as TNF superfamily modulation [ 92 ], vaccination and adoptive DC transfer therapy [ 93 , 94 ], and IDO1 blockade [ 82 , 83 ] with or without immune checkpoint molecule inhibitors association [ 95 , 96 , 97 ]. Finally, targeting CD8 + regulatory T-cells has also been proposed [ 98 ].…”
Section: Tumor-infiltrating Pdcs In Solid Cancersmentioning
confidence: 99%
“…Targeting those immune checkpoint molecules is a common anti-tumor strategy currently used in cancers. Other strategies are also proposed as TNF superfamily modulation [ 92 ], vaccination and adoptive DC transfer therapy [ 93 , 94 ], and IDO1 blockade [ 82 , 83 ] with or without immune checkpoint molecule inhibitors association [ 95 , 96 , 97 ]. Finally, targeting CD8 + regulatory T-cells has also been proposed [ 98 ].…”
Section: Tumor-infiltrating Pdcs In Solid Cancersmentioning
confidence: 99%
“…SKOV-3 and K562 were purchased from the ATCC, and IGROV-1 and OVCAR-3 were kindly provided by Prof. Dr. OC Boerman, Department of Nuclear Medicine, Radboud University Medical Center, Nijmegen, the Netherlands. Primary patient-derived OC cell line ASC 009 was generated from ascites material obtained from the Gynecologic Oncology Biobank of the Radboud University Medical Center by NTRC in Oss, the Netherlands as described, 17 and kindly provided by Guido Zaman. This study was approved by the Radboudumc Committee for Medical Research Ethics (CMO 2018/4845), and written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical research showed that the combination of melatonin and 1-MT has a synergistic effect combined with tumor-specific immunotherapy and seems to be a new and promising method of growth control of HPV-associated tumors [ 93 ]. Also, novel IDO inhibitors, LW106 and NTRC 3883-0 inhibit tumor outgrowth in-vivo, limiting IDO-dependent stroma immune resistance and proliferation of cancer stem cells within the tumor microenvironment ( Table 1 ) [ 94 , 95 ].…”
Section: Modulation Of Kynurenine Pathway Activity In the Management Of Neoplastic Diseasesmentioning
confidence: 99%
“…Its administration inhibits tumor growth in a B16-F10 melanoma mouse model [ 153 ]. Likewise, LW-106 demonstrated a potent antitumor activity based on a similar mechanism in the IDO-overexpressing melanoma mouse model, while NTRC 3883-0 in ovarian cancer cell culture and melanoma mouse model ( Table 1 ) [ 94 , 95 ].…”
Section: Modulation Of Kynurenine Pathway Activity In the Management Of Neoplastic Diseasesmentioning
confidence: 99%